When the Facts and the Law Are Against You, Argue the Genes?: A Pragmatic Analysis of Genotyping Mitigation Defenses for Psychopathic Defendants in Death Penalty Cases - Brett Walker (Washington University Law Review, 2013)
The penalty phase in a capital case represents the most challenging, yet important part of the trial. Once a trial progresses to this stage, the jury has already rendered a guilty verdict, and the defense attorney faces the uphill battle of humanizing the defendant in order to distance him or her from the heinous act. Such a task proves especially difficult in cases involving a psychopathic defendant. This individual‘s emotionally detached, manipulative, and callous nature severely inhibits the attorney‘s ability to connect with the defendant. Even more troubling, the combination of these characteristics exudes an air of remorselessness to the jury. In this situation, the attorney faces a difficult situation in which he or she is constitutionally required to provide a humanizing composite picture of the defendant for the mitigation phase, but such a task seems nearly impossible when the client appears to be devoid of all characteristics we typically associate with human nature. Without some creative form of mitigation evidence, the jury will undoubtedly find this defendant more monster than human and impose the death penalty. In the past, such a situation may have ended with the defendant receiving the death penalty, or, in some rare instances, the case getting reversed for a Sixth Amendment violation for ineffective assistance of counsel. New advances in neuroscience technology over the last twenty years, however, have allowed criminal defense attorneys to identify a wide array of brain abnormalities that may assist in mitigation. While brain scanning technology has received the majority of research and application in criminal cases in recent years, relatively new to the courts is genetic research that has revealed a genetic predisposition for one‘s propensity for violence. Specifically, independently conducted research studies in the field of behavioral genetics suggest that the combination of genetic predisposition and an abusive environment may significantly contribute to violent antisocial behavior, including psychopathy. While past scholarship and recent public debate have focused upon the long-term normative implications of neuroscience and culpability, this Note explores genotyping‘s practical application in current capital cases involving psychopathic defendants.This Note avoids any normative discussions concerning morality and culpability in light of the new advances in neuroscience. Instead, it focuses more on the pragmatic considerations that capital defense attorneys routinely encounter while attempting to fulfill their constitutional obligations. Even though this Note does not propose genotyping defenses as the ultimate panacea for mitigation difficulties,the Note does advocate that genotyping evidence, combined with psychological evaluation, family history evidence, and expert psychological testimony, could provide a potentially powerful mitigation tool to capital defense attorneys when representing a psychopathic defendant. This Note proceeds in four parts. Part I defines psychopathy and discusses potential causes and diagnostic devices used to identify this disorder. Part II explores the basic structure of capital cases, common mitigation techniques, and potential deficiencies in mitigation evidence when applied to psychopathic defendants. Part III discusses how neuroimaging and genotyping may account for some of the deficiencies in mitigation. Part IV conducts an in-depth case analysis, examines the potential costs and benefits of using genotyping defenses, and provides recommendations for use in future trials.
Keywords: genotyping; defense attorney; mitigation; defense